Regulating Statistics in the Age of Data Abundance - Bromley, Catherine (International Journal of Population Data Science, 2019)
Background with rationale The Office for Statistics Regulation is the UK’s independent regulator of official statistics produced by public sector bodies. The Code of Practice for Statistics sets out our expectations for statistics to be produced in a trustworthy way, be of high quality, and to serve the public good by informing answers to society’s important questions. We now live in a world of increasingly abundant data. Statistics producers need to adapt to this environment, and so do we as regulators. Approach The Code of Practice was updated in 2018 with new provisions to maximise the potential use of data for both citizens and organisations, and to make data available for wider reuse with appropriate safeguards. We have supplemented our commitment to these provisions with a review of data sharing and linking in government, new regulatory guidance on data governance, an increased focus on data access challenges (particularly users of English health data), and by putting data at the heart of our regulatory vision (published in summer 2019). These steps build on our existing work around admin data quality. Overview The National Statistician’s response to our data sharing and linkage review included many welcome commitments and a major review of data linkage methodology is now underway. A data linkage community is developing across government. However, we have raised concerns about ongoing difficulties with admin data sharing between departments, resource constraints, and the limited extent of public engagement about data sharing and use. Conclusions Our regulatory approach to data is evolving and we are building new relationships with organisations with an interest in data beyond the statistics world. Our work to support users to access admin data may yet require more direct interventions to bring about the outcomes we desire. We are keen to share our experiences with admin data users.